Altered Interoceptive Sensibility in Adults With Chronic Tic Disorder - Narapareddy, Ashruta; Eckland, Michelle R.; Riordan, Heather R.; Cascio, Carissa J.; Isaacs, David A. (Frontiers in Psychiatry, 2022)
Background Interoception refers to the sensing, interpretation, integration, and regulation of signals about the body’s internal physiological state. Interoceptive sensibility is the subjective evaluation of interoceptive experience, as assessed by self-report measures, and is abnormal in numerous neuropsychiatric disorders. Research examining interoceptive sensibility in individuals with chronic tic disorders (CTDs), however, has yielded conflicting results, likely due to methodologic differences between studies and small sample sizes. Objective We sought to compare interoceptive sensibility between adults with CTD and healthy controls, adjusting for co-occurring psychiatric symptoms, and to examine the relationship of interoceptive sensibility with other CTD clinical features, in particular, premonitory urge. Methods We recruited adults with CTDs and sex- and age-matched healthy controls to complete the Multidimensional Assessment of Interoceptive Awareness, Version 2 (MAIA-2), as well as a battery of measures assessing psychiatric symptoms prevalent in CTD populations. CTD participants additionally completed scales quantifying tic severity, premonitory urge severity, and health-related quality of life. We conducted between-group contrasts (Wilcoxon rank-sum test) for each MAIA-2 subscale, analyzed the effect of psychiatric symptoms on identified between-group differences (multivariable linear regression), and examined within-group relationships between MAIA-2 subscales and other clinical measures (Spearman rank correlations, multivariable linear regression). Results Between adults with CTD (n = 48) and healthy controls (n = 48), MAIA-2 Noticing and Not-Worrying subscale scores significantly differed. After adjusting for covariates, lower MAIA-2 Not-Worrying subscale scores were significantly associated with female sex (β = 0.42, p < 0.05) and greater severity of obsessive-compulsive symptoms (β = –0.028, p < 0.01), but not with CTD diagnosis. After adjusting for severity of tics and obsessive-compulsive symptoms, a composite of MAIA-2 Noticing, Attention Regulation, Emotional Awareness, Self-Regulation, Body Listening, and Trusting subscales (β = 2.52, p < 0.01) was significantly associated with premonitory urge. Conclusion Study results revealed three novel findings: adults with CTD experience increased anxiety-associated somatization and increased general body awareness relative to healthy controls; anxiety-associated somatization is more closely associated with sex and obsessive-compulsive symptoms than with CTD diagnosis; and increased general body awareness is associated with greater severity of premonitory urges.